Development of the swimming acorn worm Glandiceps hacksi: similarity to holothuroids. Issue 3 (8th April 2014) - Urata, Makoto; Iwasaki, Sadaharu; Ohtsuka, Susumu; Yamaguchi, Masaaki
SUMMARY Spawnings of Glandiceps hacksi (Hemichordata: Enteropneusta) were stimulated in the laboratory by a brief increase in temperature, and the development from fertilization through metamorphosis is described for the first time for a member of the family Spengelidae. When fertilized, the spawned female gametes, which are primary oocytes, rapidly raise a fertilization membrane and undergo two maturation divisions. Holoblastic, radial cleavage produces a blastula; a gastrula then forms by invagination from the vegetal pole, and the blastopore closes soon thereafter. In previously described enteropneust embryos, the archenteron buds off the protocoel before the latter connects to the exterior via the proboscis pore. By contrast, in G. hacksi the archenteron precociously connects with the exterior before the protocoel forms. Soon thereafter, the embryo becomes uniformly ciliated and then hatches from the fertilization envelope at approximately 32 h (15°C culture temperature). At day 3 of development, the protocoel separates from the gut, which establishes a mouth opening to the exterior; by this time, the gut has differentiated into an esophagus, a stomach, and an intestine that opens posteriorly as an anus. The larva grows to form a tornaria with distinctive pigment patches along its ciliary bands.